The Relationship between Self-efficacy and Breastfeeding, Tehran, Iran - Sh Varaei; N Mehrdad; N Bahrani (Tehran University of Medical Sciences, 2009)
Background & Aim: Breastfeeding is the most cost-effective, health-promoting, and disease-preventing activity that new mothers can perform. Many researches have focused on identifying factors that influence breastfeeding initiation and duration. An important and modifiable factor is the perceived self-efficacy of mothers for breast feedings. It refers to a mother;aposs perceived ability to breastfeed her newborn and is a dominant variable in the duration of breastfeeding. The purpose of this study was to assess the relationship between self-efficacy and breastfeeding. Methods & Materials: A descriptive, longitudinal, analytic approach was used in this study. The three-part questionnaire was administered to the eligible pregnant women (437 pregnant women) who were at least in 37 weeks of gestation and intended to breastfeed. They were then contacted again at one and four months postpartum to determine their infants;apos feeding level and method. The questionnaire was re-administered to the participants at that time. Results: The results showed that 80.4 percent of participants had exclusive breastfeeding during one month. There was no significant relationship between antenatal breastfeeding self-efficacy and the breastfeeding. The self-efficacy was significantly related to breastfeeding outcomes at one month. Mothers with high self-efficacy were significantly more likely to breastfed their babies exclusively at one and four months postpartum than the mothers with low self-efficacy. Conclusion: Maternal breastfeeding self-efficacy is significantly related to breastfeeding duration and level. Measuring breastfeeding self-efficacy not only identifies high risk mothers, but also provides important information to health care providers in providing support to new mothers.